Pharmacogenomic Study of Statin-Associated Muscle Symptoms in the ODYSSEY OUTCOMES Trial. (11th May 2022) - Murphy, William A.; Lin, Nan; Damask, Amy; Schwartz, Gregory G.; Steg, P. Gabriel; Szarek, Michael; Banerjee, Poulabi; Fazio, Sergio; Manvelian, Garen; Pordy, Robert; Shuldiner, Alan R.; Paulding, Charles
Abstract : Background: Statin-associated muscle symptoms (SAMS) are the most frequently reported adverse events for statin therapies. Previous studies have reported an association between the p.Val174Ala missense variant in SLCO1B1 and SAMS in simvastatin-treated subjects; however, evidence for genetic predictors of SAMS in atorvastatin- or rosuvastatin-treated subjects is currently lacking. Methods: ODYSSEY OUTCOMES (Evaluation of Cardiovascular Outcomes After an Acute Coronary Syndrome During Treatment With Alirocumab; n=18 924) was a double-blind, randomized, placebo-controlled study evaluating the efficacy and safety of alirocumab (a PCSK9 [proprotein convertase subtilisin/kexin type 9] inhibitor) in acute coronary syndrome patients receiving high-intensity statin therapy. The goal of this pharmacogenomic analysis was to identify genetic variants associated with atorvastatin- and rosuvastatin-mediated SAMS among ODYSSEY OUTCOMES subjects who consented to participate in the genetic study (n=11 880). We performed multi-ancestry exome-wide and genome-wide association studies and gene burden analysis across 2 phenotypes (clinical SAMS [n=10 617] and creatine kinase levels [n=9630]). Results: A novel genome-wide significant association for an intronic variant (rs6667912) located within TMEM9 (odds ratio [95% CI], 1.39 [1.24–1.55]; P =3.71×10 −8 ) for patients with clinical SAMS (cases=894, controls=9723) was identified. This variant is located ≈30 kb upstream of CACNA1S, a locus associated with severe SAMS. We replicated 2 loci, at LINC0093 and LILRB5, previously associated with creatine kinase levels during statin treatment. No association was observed between p.Val174Ala (rs4149056) in SLCO1B1 and SAMS (odds ratio [95% CI], 1.03 [0.90–1.18]; P =0.69). Conclusions: This study comprises the largest discovery exome-wide and genome-wide association study for atorvastatin- or rosuvastatin-mediated SAMS to date. These novel genetic findings may provide biological/mechanistic insight into this drug-induced toxicity, and help identify at-risk patients before selection of lipid-lowering therapies.